Prevalensi dan karakteristik hipertensi pada pralansia dan lansia di Dusun Tengah, Desa Ulakan, Kecamatan Manggis - Restu Widiana, I Made; Seri Ani, Luh (E-Jurnal Medika Udayana; Vol 6 No 8 (2017): E-Jurnal Medika Udayana, 2017)
Based on the report of Puskesmas Manggis I on 2014, hypertension was the 3 rd most common disease within its coverage area with 1288 visits in a year. Although the report was based on the register of the Clinic in Puskesmas Manggis I, which does not reflect the magnitude of health problems caused by hypertension in the population. Therefore a study was needed to evaluate the magnitude of heath problems caused by hypertension and the characteristic of hypertensive patient in the coverage area of Puskesmas Manggis I. A cross-sectional study was done to the elderly and preelderly in Dusun Tengah, Ulakan Village, Manggis District, Karangasem Regency. 54 elderly and preelderly that were chosen by snowballing were included in this study. Data was collected by interview and observation during June 16 th – 20 th 2015. Collected data was analyzed using descriptive method to show the incidence of hypertension. Analysis shown that incidence of hypertension in elderly and preelderly was 51,9%. Only 50% of hypertensive respondent seek medical treatment to doctors or other healthcare provider. Therefore, early detection of hypertension in the elderly was recommended. Keywords: hypertension, prevalence , elderly, community health program, cross-sectional